Revenue and Feasibility Analysis of Celery (Apium Graveolens L.) in Lingkar Selatan Village Paal Merah District Jambi City. Issue 1 (March 2021) - Suharyon,; Edi, S
Abstract: The research objective was to analyze the income and feasibility of cultivating celery in the production centers. The research was conducted in Lingkar Selatan Village, Paal Merah District, Jambi Province in July 2018. The data collected included primary data in the form of information from farmers as well as secondary data and conditions of the research area, the potential of social and economic. Primary data were collected using survey techniques, interviews with farmers and key information using a questionnaire. The sample was determined randomly from the population of celery farmers at the study site, totaling 25 cooperator farmers. The data analysis technique included tabulation analysis which is used to understand the farmers' financial farming conditions, and the economic feasibility analysis used the R / C ratio. The results of research on celery farming showed that this business was profitable with a total profit Rp. 11, 121, 000, -. BEP calculation, the BEP unit is 558 kg, the rupiah BEP is Rp. 14, 721, and the R / C ratio value is 1.17, so it can be concluded that the celery farming in this study is profitable and feasible to continue.